How Entrepreneurs Work: A Psychodynamic Reading of Work Organization of Entrepreneurs Group - Guimarães Júnior, Edward Humberto (REGEPE Entrepreneurship and Small Business Journal, 2019)
The entrepreneurial action has been highly valued in the current economic, political and social model, but few studies consider entrepreneurs as workers that they are. Due to this situation, the objective of this study is to describe the work organization of the entrepreneurs, privileging the understanding of the subjective aspects mobilized by them from concrete work situations, taking as a theoretical-methodological approach the Psychodynamics of Work. Four collective sessions were held with a group of eight entrepreneurs, with a total duration of approximately 12 hours. The data collection instrument was a semi-structured questionnaire. The sessions were recorded on video, transcribed and then analyzed using the Content Analysis technique. It can be observed that the form of organization of the work of the entrepreneur differs from most of the workers, being characterized by a routine of contingencies and preparation, requiring a greater capacity of planning and flexibility in the accomplishment of its labor activities. In general, entrepreneurs have a daily agenda full of commitments, which leads to an intense workload. Although, they have the power to make changes in the organization of their work, in their activities and schedules, providing greater freedom and autonomy in daily work. It was verified that, in creating the business itself, the entrepreneurs become active agents in the modeling of both the work itself and its organizations, providing them with a better psychic discharge. However, the freedom attributed to entrepreneurs' work is limited by government bureaucracy, socio-professional relations and the labor market.